Types of contraceptives practiced by the women attending model family planning clinic at Dhaka Medical College Hospital, Dhaka - Mahmood, AR; Hoque, SR; Ara, S; Karim, SR; Ferdousi, SK; Sultana, R (Journal of Dhaka Medical College, 2012)
DOI: http://dx.doi.org/10.3329/jdmc.v20i2.10531 J. Dhaka Med. Coll. 2011; 20(2): 112-115